A Cytokinin Signaling Type-B Response Regulator Transcription Factor Acting in Early Nodulation. Issue 3 (6th May 2020) - Tan, Sovanna; Sanchez, Myriam; Laffont, Carole; Boivin, Stéphane; Le Signor, Christine; Thompson, Richard; Frugier, Florian; Brault, Mathias
Abstract : A Medicago truncatula cytokinin-signaling transcription factor is required for early symbiotic nodulation and to regulate key Nod factor signaling and endoreduplication genes. Abstract: Nitrogen-fixing root nodulation in legumes challenged with nitrogen-limiting conditions requires infection of the root hairs by soil symbiotic bacteria, collectively referred to as rhizobia, and the initiation of cell divisions in the root cortex. Cytokinin hormones are critical for early nodulation to coordinate root nodule organogenesis and the progression of bacterial infections. Cytokinin signaling involves regulation of the expression of cytokinin primary response genes by type-B response regulator (RRB) transcription factors. RNA interference or mutation of MtRRB3, the RRB-encoding gene most strongly expressed in Medicago truncatula roots and nodules, significantly decreased the number of nodules formed, indicating a function of this RRB in nodulation initiation. Fewer infection events were also observed in rrb3 mutant roots associated with a reduced Nod factor induction of the Early Nodulin 11 ( MtENOD11 ) infection marker, and of the cytokinin-regulated Nodulation Signaling Pathway 2 ( Mt NSP2 ) gene. Rhizobial infections correlate with an expansion of the nuclear area, suggesting the activation of endoreduplication cycles linked to the cytokinin-regulated Cell Cycle Switch 52A ( Mt CCS52A ) gene. Although no significant difference in nucleus size and endoreduplication were detected in rhizobia-infected rrb3 mutant roots, expression of the MtCCS52A endoreduplication marker was reduced. As the MtRRB3 expression pattern overlaps with those of MtNSP2 and MtCCS52A in roots and nodule primordia, chromatin immunoprecipitation-quantitative PCR and protoplast trans-activation assays were used to show that MtRRB3 can interact with and trans-activate MtNSP2 and MtCCS52A promoters. Overall, we highlight that the MtRRB3 cytokinin signaling transcription factor coordinates the expression of key early nodulation genes.